2014
DOI: 10.1111/jawr.12215
|View full text |Cite
|
Sign up to set email alerts
|

Price Determination and Efficiency in the Market for South Platte Basin Ditch Company Shares

Abstract: Water scarcity presents an obstacle to economic development in the western United States. Water rights markets help improve water allocation, allowing states to derive the highest economic benefit from available resources, and supporting new uses and economic development. However, the implicit (marginal) prices of water rights attributes are uncertain. To address this problem, we apply econometric analysis to a unique dataset to estimate the implicit values that market participants place on the attributes of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 26 publications
1
16
1
Order By: Relevance
“…Although it has been frequently reported that the price of water transfer and the volume of water being traded are correlated [12,61,66], the influence of Quantity according to PVI ranking is much stronger than our anticipation. This may be a response to the economics of scale phenomenon in trade.…”
Section: Relative Importance Of Individual Variablescontrasting
confidence: 67%
See 1 more Smart Citation
“…Although it has been frequently reported that the price of water transfer and the volume of water being traded are correlated [12,61,66], the influence of Quantity according to PVI ranking is much stronger than our anticipation. This may be a response to the economics of scale phenomenon in trade.…”
Section: Relative Importance Of Individual Variablescontrasting
confidence: 67%
“…That is, transaction cost per unit volume of water decreases as traded water volume increases. Consequently, water price falls as transactions involve greater size of water, which has been discussed in previous studies [12,66,67]. This result also indicates that the proxy variable State was very important as hypothesized, which implies that the price variation between states may largely be due to their differences in factors such as state laws, institutional arrangements and major water projects.…”
Section: Relative Importance Of Individual Variablessupporting
confidence: 63%
“…Senior water rights transfers exhibited higher transaction costs, though senior rights did not influence completion times. Because senior rights are more valuable (Payne et al, 2014), applicants would rationally spend more on transaction costs to complete a transfer and opposing parties would rationally spend more to protect their water rights from injury.…”
Section: Discussionmentioning
confidence: 99%
“…The OLS water rights pricing model includes several types of water rights, two of which do not exist in all water divisions: certain Denver Basin groundwater rights legally termed "not nontributary groundwater" are found only in the South Platte and Arkansas River divisions, while sales of shares in a desirable mutual ditch company, the Farmers Reservoir and Irrigation Company, only exist in the South Platte River Division (Payne et al, 2014;Trout et al, 2011).…”
Section: 1029/2019wr025507mentioning
confidence: 99%
“…Climatic conditions influence the availability of the resource, challenging predictions for what will be available to trade or sell. The way water moves through the landscape can limit possible transactions, related to above and below ground connectivity or to conveyance and related infrastructural issues that can arise when one attempts to move water to a new use (Payne, Smith, and Landry )—even with the South Platte’s intricate and extensive water delivery system.…”
Section: Environmental Justice Water Commodification and Market Tramentioning
confidence: 99%